Evaluasi Dan Rancangan Sistem Ventilasi Pada Tambang Batubara Bawah Tanah Lubang BT 02 PT. Nusa Alam Lestari, Kota Sawahlunto, Sumatera Barat. - Carles Trisis Caniago; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Nusa Alam Lestari is an underground coal mining company located in Batu Tanjung Village, Talawi District, Sawahlunto City, West Sumatra. This research aims to reveal the quality and quantity of air, reveal the maximum ventilation requirements that can be supplied by fans according to the currently installed specifications to channel fresh air to the front work and describe the current model of the ventilation system and the design of the future ventilation system according to changing field conditions in the hole. BT 02 PT Alam Nusa Lestari. From the results of temperature measurements in the BT 02 Utama (BT02U) 30.10c hole and the BT 02 Companion hole (BT02P) 280c. With an average humidity in BT02U which is 97.74% and in BT02P 89.0%. Based on Kepmen 1827 k / MEM / 30/2018 and KepDirJen Minerba of the Ministry of Energy and Mineral Resources Number 185.K / 37.04 / DJB / 2019. The specified temperature values are 180C-270C and a maximum relative humidity of 85%. From the calculation results, the air requirement in the BT02 U hole is 11,1165 m3 / s, the BT 02 P hole is 8,1166 m3 / s, and the air requirement to dilute methane gas from the BT 02 hole is 2,397 m3 / s, the oxygen content is 20.9% and It is in accordance with the air requirements for workers stipulated in the Ministerial Decree 1827. Dirty air resulting from mining activities is sucked out through the ventilation holes and replaced with clean air that enters through holes BT 02 U and BT 02 P that have been installed with blow blowers.